Stability conditions of limit cycle for Gompertz Autoregressive model - Nezar E. Ali; Azher A. Mohammad (Tikrit Journal of Pure Science)
In this paper, we suggest Gompertz Autoregressive model by using the cumulative distribution function of Gompertz distribution and, the aim of this paper is studying and finding the stability conditions of a limit cycle for the Gompertz Autoregressive model with period,  with giving some examples for Gompertz AR (1) to explain the orbital stable or the orbital unstable with plots the trajectories with different initial values.